Conceptualizing addictive-like eating: A qualitative analysis. (1st October 2019) - Paterson, Carley; Lacroix, Emilie; von Ranson, Kristin M.
Abstract: Debates regarding addictive-like eating have generated several conceptualizations of this construct. Qualitative research helps ensure that conceptualizations capture how individuals may experience addictive-like eating. In this study, we conducted semi-structured interviews with ten participants who identified themselves as addicted to food, or to food and eating, to determine how they conceptualized their addictive-like eating. Using thematic analysis, we identified four themes: (1) Social Environment, describing how past and present social environments affected addictive-like eating; (2) Situational Cues, encompassing situational contributions to addictive-like eating; (3) Persistent Cognitions, including preoccupation with food and loss of control; and (4) Impact of Weight, encompassing weight gain and its perceived impact on health, body image, and distress. Participants described properties specific to their preferred foods, as well as environmental and cognitive factors contributing to addictive-like eating. These descriptions were not completely captured by either the substance-based "food addiction" or behavioural "eating addiction" frameworks, though characteristics consistent with both were present. Further, existing scales of addictive-like eating do not assess the impact of social and situational cues, suggesting a need for new or revised measures. We propose a working definition of addictive-like eating that incorporates the characteristics described.